2012
DOI: 10.1097/tp.0b013e3182466248
|View full text |Cite
|
Sign up to set email alerts
|

Can Immune Cell Function Assay Identify Patients at Risk of Infection or Rejection? A Meta-Analysis

Abstract: The current evidence suggests that CICFA is not able to identify individuals at risk of infection or rejection. Additional studies are still needed to clarify the usefulness of this test for identifying risks of infection and rejection in transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 33 publications
2
64
2
Order By: Relevance
“…In contrast to this, Table 1 shows that there was no significant difference in the ATP levels from CD4 + T cells before and after the therapy. The results were not consistent with our expectation; a possible reason might be that the sensitivity of the ImmuKnow method has been reported to be low (Husain et al, 2009;Ling et al, 2012), and thus might not detect the change associated with an increase in immune function. Therefore, we concluded that the detection of ATP levels from CD4 + T cells by the Immuknow TM -Cylex ® assay did not reflect the actual immune status of patients with renal cancer after surgery.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In contrast to this, Table 1 shows that there was no significant difference in the ATP levels from CD4 + T cells before and after the therapy. The results were not consistent with our expectation; a possible reason might be that the sensitivity of the ImmuKnow method has been reported to be low (Husain et al, 2009;Ling et al, 2012), and thus might not detect the change associated with an increase in immune function. Therefore, we concluded that the detection of ATP levels from CD4 + T cells by the Immuknow TM -Cylex ® assay did not reflect the actual immune status of patients with renal cancer after surgery.…”
Section: Discussioncontrasting
confidence: 56%
“…However, as shown in Figure 1, our results demonstrated that the ATP levels were not significantly different at the different time points. A possible reason for this might be that the ImmuKnow method has been found to exhibit low sensitivity toward the detection of ATP content (Husain et al, 2009;Ling et al, 2012); this assay might not therefore recognize the immune function changes in patients with renal cancer. We expected that patient immunity would have decreased 10 days after the surgery; however, Figure 1 shows that the intracellular ATP levels from CD4 + T cells at this time were significantly higher than at other time points.…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative incidence curves were constructed for study outcomes (overall and bacterial infection and CMV diseases) with death treated as a competing risk, and differences between groups were compared with the log-rank test. Uni-and multivariate Cox regression models were used to evaluate the association between iATP categories at each point (baseline and months 1 and 6 after transplantation) and outcomes throughout the following periods (early [first month], intermediate [months [1][2][3][4][5][6], and late periods [months [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], respectively) [1]. Associations were expressed as hazard ratios (HRs) and 95% confidence intervals (CIs).…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of the 13 cases of CMV disease diagnosed in the intermediate period in which iATP levels at month 1 were available is provided as Supporting Information (Table S2). Finally, there were no significant differences in the incidence of infection at the end of the late period (i.e., months [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] according to the CMI response at month 6.…”
Section: Risk Of Infection Across Different Categories Of CMI Responsementioning
confidence: 99%
See 1 more Smart Citation